Coefficient of rill and interrill erodibility of cohesive Ultisols estimated by soil color - Dantas, Jussara Silva; Martins Filho, Marcílio Vieira; Marques Júnior, José; Resende, José Maria do Amaral; Teixeira, Daniel De Bortoli; Barbosa, Ronny Sobreira; Siqueira, Diego Silva (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to estimate the rill and interrill erodibility coefficient through soil color parameters. Three areas were selected, which were cultivated with soybean in cohesive Ultisols of the eastern region of the state of Maranhão, Brazil. In each area, 121 samples were collected at a depth of 0.00–0.20 m. The values of diffuse reflectance spectroscopy in the visible range were determined, in order to obtain the values of hue, value, and chroma. From these color constituents, the redness index was calculated for each sample. Models were developed to evaluate the effect of each color component on rill and interril erodibility. These components showed R2 ranging from 0.37 to 0.70. The generated models obtained R2 of 0.70 and 0.73 for interill and rill, respectively. Soil color determined by diffuse reflectance spectroscopy can be used as an alternative method to estimate the erodibility coefficient of cohesive Ultisols.